Pattern of Valvular Involvement in Rheumatic Heart Disease (RHD) Patients attending Referral Cardiac Center in Nepal - KC, MB; Kansakar, S; Bhatta, YKD; Rajbhandari, Rajib; Maskey, A; Sharma, D; Malla, R; Limbu, Y; Regmi, SR (Nepalese Heart Journal, 2004)
Rheumatic heart disease (RHD) is very common in developing countries. It is one of the commonest cardiac problems in Nepal. It is more common in rural areas than in the cities. We performed a retrospective study of RHD patients attending and undergoing echocardiography in Shahid Gangalal National Heart Centre (SGNHC) from January 2002 to December 2002. There were a total of 1843 RHD patients among which 787 (42.8%) were males and 1056 (57.2%) were females.